Vascular mapping for the decision of hemodialysis access method: Case report. Issue 1 (May 2019) - Uchino, Takashi; Nakai, Hiromasa; Ichihashi, Hiroaki; Sasaki, Tsukasa; Azuma, Nakanobu
Preoperative ultrasound vascular mapping was performed to determine the surgical method for two cases where standard arteriovenous fistula was not possible. In case 1, the previous arteriovenous fistula of the left arm was occluded, and arteriovenous graft of the right arm was thrombosed after frequent percutaneous transluminal angioplasty. Contrast medium was contraindicated because of allergy. Using preoperative ultrasound vascular mapping, we were able to establish the appropriate surgical method. In case 2, hemodialysis was started by catheter insertion, and then access creation was planned. This case was treated with steroids due to a bullous pemphigoid disease and there was a high risk of infection, which precluded the use of synthetic grafts. There was also the possibility of delay in healing due to malnutrition. Therefore, appropriate surgical method was tailored by using preoperative ultrasound vascular mapping. Ultrasound vascular mapping was useful for determining the surgical creation of an appropriate access for facilitating hemodialysis cannulation.